429 Effects of endophyte strain on performance of beef cows grazed on summer stockpiled tall fescue pastures. (7th December 2018) - Langford, T; Barry, G; Sims, W; Hardin, K; Fiske, D; Pent, G; Wilson, T
Abstract: The objectives of this experiment were to evaluate forage characteristics of wild-type endophyte-infected tall fescue (KY-31 ) and novel endophyte-infected tall fescue (MaxQ ) within summer stockpiled (SS ) pastures and to measure the performance of fall-calving beef cows grazed on these pastures. Pregnant Simmental x Angus cows (64 total) were stratified by BW, BCS, and expected calving date and allotted into 1 of 10 groups. Groups were assigned to either KY-31 or MaxQ SS pastures. Forage growth accumulated from April to initiation of strip-grazing on August 31, 2017. During the 52 d grazing period, cows were grazed on treatment pastures from 24 ± 12 d prepartum to 28 ± 12 d postpartum and calved on treatment pastures. Forage quadrats were clipped from the grazed and ungrazed portions of each pasture to determine weekly forage mass (FM ). Total ergot alkaloid (TEA ) concentrations were analyzed for all pastures at the beginning of the experiment and bi-weekly for KY-31. Cow BW was recorded on 2 consecutive d and BCS determined at the start and end of the experiment. Calf BW was recorded within 24 h of birth and on 29 ± 12 d of age. Milk production was estimated via the weigh-suckle-weigh technique at 29 ± 12 d postpartum. Initial TEA concentrations were decreased ( P < 0.001) for MaxQ relative to KY-31 and did not differ ( P < 0.48) in KY-31 over time. No differences ( P ≥ 0.46) in grazed or ungrazed FM between fescue strains were observed. Cow BW and BCS at the beginning and end of grazing were not different ( P ≥ 0.40) by fescue strain. Calving date, calf BW, calf ADG, and milk production was not different ( P ≥ 0.13) by treatment. Grazing MaxQ rather than KY-31 SS pastures resulted in no improvements in cow/calf performance under the conditions of our experiment.